Fatigue Life Estimation Based On Continuum Mechanics Theory With Application Of Genetic Algorithm - M., Kamal; M. M., Rahman (Universiti Malaysia Pahang, 2015)
In recent years research on fatigue estimation methods has focused on developing the capability to handle complex multiaxial loading conditions. The present study presents the development of a new fatigue life estimation model using the concepts of continuum mechanics with a critical plane based approach, where a genetic algorithm is used to estimate the coefficients of the model. Experimental fatigue lives for steel alloy C40 for in-phase and out-of-phase loading conditions are used to calibrate and analyze the accuracy of the proposed model. Finite element analysis is used to determine the experimental fatigue life of steel alloy C40 published in literature for validation purposes. The proposed model is simple to apply as it does not need to determine any new material constants or properties for the new model. Fatigue life prediction from the proposed model shows good agreement with experimental results for in-phase and outof-phase multiaxial loading.